Metatheory and Classification of Digital Human Rights and Freedoms - G. V. Alexeyev (Теоретическая и прикладная юриспруденция)
Humanism is a doctrinal metanarrative that defines ideas about human rights and freedoms. Natural law is relevant in the digital world, since each specific individual is quite rationally interested in ensuring that the humanistic paradigm prevails over abstract technologies. The theory of individual freedom and legal equality, when faced with computer information processing algorithms, gives rise to paradoxes and oxymorons. The obvious contradictions in the moralism of the virtual world and real justice are complemented by the paradoxical conclusions of lawyers about the legal personality of robots with artificial intelligence and the similarity of the laws for the real world and cyberspace. The methodology for refuting neoliberal utopias and totalitarian fantasies that shape the imaginary cyberspace or deny its existence can vary from classical dialectics to modern narrative analysis, but methods of participant observation demonstrate the existence of real and virtual rights and freedoms of man and citizen in a digital world. We believe that cyberspace was formed due to the implementation of natural freedom of creativity, on the basis of which, in the process of digitalization, real digital rights were recognized for individuals. While information society institutions are being formed with the help of artificial intelligence within the cyberspace, a complex of virtual digital rights should be recognized by the legislator. The realization of virtual digital rights is possible without human participation, but legal meaning of such rights requires from individuals or corporations some actions that lead to legally significant consequences beyond the virtual dimensions of the real world.